2019
DOI: 10.1038/s41467-019-10738-4
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals negative capacitance transistors

Abstract: The Boltzmann distribution of electrons sets a fundamental barrier to lowering energy consumption in metal-oxide-semiconductor field-effect transistors (MOSFETs). Negative capacitance FET (NC-FET), as an emerging FET architecture, is promising to overcome this thermionic limit and build ultra-low-power consuming electronics. Here, we demonstrate steep-slope NC-FETs based on two-dimensional molybdenum disulfide and CuInP 2 S 6 (CIPS) van der Waals (vdW) heterostruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
163
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(188 citation statements)
references
References 36 publications
(29 reference statements)
1
163
1
Order By: Relevance
“…), or 1D (such as carbon nanotube (CNT), graphene nanoribbon (GNR) etc. ), generating numerous "NC-FETs" in the past several years [8][9][10][11][12][13][14][15] . However, none of them exhibit SSs that are noticeably smaller than 60 mV per decade and simultaneously free of hysteresis during both AC and DC operations (see Supplementary Table 1).…”
mentioning
confidence: 99%
“…), or 1D (such as carbon nanotube (CNT), graphene nanoribbon (GNR) etc. ), generating numerous "NC-FETs" in the past several years [8][9][10][11][12][13][14][15] . However, none of them exhibit SSs that are noticeably smaller than 60 mV per decade and simultaneously free of hysteresis during both AC and DC operations (see Supplementary Table 1).…”
mentioning
confidence: 99%
“…The device shown in Figure 3e has a typical structure of ferroelectric FET for studying the so‐called negative‐capacitance effect. [ 42 ] While measuring the transfer curve of the device, three types of capacitors are involved and the corresponding capacitances are (left part in Figure 1d): gate insulator capacitance (C i ), here it is a series connection of ferroelectric capacitor (here CIPS) and h‐BN capacitor, and channel capacitance (here MoS 2 , C c ). It has been found that when the capacitance parameters satisfy the condition | C i | > C c , a dielectric matching can be reached, and the hysteresis in the I DS – V GS curve is absent.…”
Section: Figurementioning
confidence: 99%
“…Copper indium thiophosphate, CuInP 2 S 6 (CIPS), a van der Waals (vdW) layered material that is ferrielectric at room temperature [20][21][22][23][24] has been explored for NC due to its compatibility with other 2D materials for advanced heterostructures. [25] The polarization of CIPS arises from the noncentrosymmetric z displacement of Cu and In atoms with respect to the P 2 S 6 sublattice. [26,27] Recently, density functional theory (DFT) demonstrated the presence of two iso-symmetric polar phases.…”
Section: Introductionmentioning
confidence: 99%